Rechargeable Capacities and Polarizations of LizNi0.75Co0.15Al0.05Mg0.05O2-δ versus LizNi0.8Co0.15Al0.05O2-δ for Lithium-Ion Batteries. Issue 12 (19th September 2017) - Makimura, Yoshinari; Sasaki, Tsuyoshi; Nonaka, Takamasa; Nishimura, Yusaku F.; Uyama, Takeshi; Okuda, Chikaaki; Takeuchi, Yoji
Abstract : A comparative study of Liz Ni0.75 Co0.15 Al0.05 Mg0.05 O2-δ (NCA-Mg derivatives) and Liz Ni0.8 Co0.15 Al0.05 O2-δ (NCA derivatives) having rock-salt domain was performed to understand the resistance-increase owing to materials degradation of NCA and the improvement by Mg-substitution. This paper focuses on fundamental aspect of materials degradation of NCA-Mg in comparison to that of NCA. NCA-Mg derivatives were prepared and the structures were determined by a Rietveld method of the XRD patterns. Charge and discharge operations of NCA-Mg derivatives were carried out in lithium cells at C/10-rate at 20°C and polarizations were estimated by Galvanostatic Intermittent Titration Technique (GITT) measurement. NCA-Mg with nearly stoichiometric composition gives smaller rechargeable capacity and larger polarization than those of NCA. This suggests that Mg-substitution in NCA exhibits some drawbacks in the initial state of charge and discharge operation. Mg-substitution in NCA is, however, effective to improve the cycling life. NCA-Mg derivatives show capacity retention of above 90% after 30 cycles irrespective of y-values corresponding to the amount of rock-salt domains at C/10-rate in lithium cells, while NCA derivatives of y > 0.02 deteriorate rapidly upon charge and discharge cycles. This is associated with the smaller polarization-increase of NCA-Mg derivatives than NCA derivatives, which is ascribed to improved lithium-ion mobility in the rock-salt domains owing to Mg-substitution in NCA.